A survey of authors publishing in four megajournals - Solomon,David J. (PeerJ, 2014)
Aim. To determine the characteristics of megajournal authors, the nature of the manuscripts they are submitting to these journals, factors influencing their decision to publish in a megajournal, sources of funding for article processing charges (APCs) or other fees and their likelihood of submitting to a megajournal in the future. Methods. Web-based survey of 2,128 authors who recently published in BMJ Open, PeerJ, PLOS ONE or SAGE Open. Results. The response rate ranged from 26% for BMJ Open to 47% for SAGE Open. The authors were international, largely academics who had recently published in both subscription and Open Access (OA) journals. Across journals about 25% of the articles were preliminary findings and just under half were resubmissions of manuscripts rejected by other journals. Editors from other BMJ journals and perhaps to a lesser extent SAGE and PLOS journals appear to be encouraging authors to submit manuscripts that were rejected by the editor’s journals to a megajournal published by the same publisher. Quality of the journal and speed of the review process were important factors across all four journals. Impact factor was important for PLOS ONE authors but less so for BMJ Open authors, which also has an impact factor. The review criteria and the fact the journal was OA were other significant factors particularly important for PeerJ authors. The reputation of the publisher was an important factor for SAGE Open and BMJ Open. About half of PLOS ONE and around a third of BMJ Open and PeerJ authors used grant funding for publishing charges while only about 10% of SAGE Open used grant funding for publication charges. Around 60% of SAGE Open and 32% of PeerJ authors self-funded their publication fees however the fees are modest for these journals. The majority of authors from all 4 journals were pleased with their experience and indicated they were likely to submit to the same or similar journal in the future. Conclusions. Megajournals are drawing an international group of authors who tend to be experienced academics. They are choosing to publish in megajournals for a variety of reasons but most seem to value the quality of the journal and the speed of the review/publication process. Having a broad scope was not a key factor for most authors though being OA was important for PeerJ and SAGE Open authors. Most authors appeared pleased with the experience and indicated they are likely to submit future manuscripts to the same or similar megajournal which seems to suggest these journals will continue to grow in popularity.
Keywords: Open access; Megajournals; Survey; Authors